2019
DOI: 10.1101/684142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dysfunction of ventral tegmental area GABA neurons causes mania-like behavior

Abstract: The ventral tegmental area (VTA), an important source of dopamine, regulates goal-and reward-directed and social behaviors, wakefulness and sleep. Hyperactivation of dopamine neurons generates behavioral pathologies. But any roles of non-dopamine VTA neurons in psychiatric illness have been little explored. Lesioning or chemogenetically inhibiting VTA GABAergic (VTA Vgat ) neurons generated persistent wakefulness with mania-like qualities: locomotor activity was increased; sensitivity to D-amphetamine was heig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…However, acute opto-inhibition during wake, did affect consummatory licking behavior similarly to what has been previously described for Vgat ( Van Zessen et al., 2012 ) and Dat ( Hughes et al., 2020 ; Lee et al., 2020 ) neurons ( Figure S4 ). In addition, chronic opto-inhibition of each population during rest (laser on continuously for 4 h, beginning in quiet wake) did alter sleep architecture in drastically opposing ways, consistent with chemogenetic and sustained opto-manipulation results from previous studies ( Eban-Rothschild et al., 2016 ; Yu et al., 2019a , b ; Figure S5 ).
Figure 4 Sleep was not disrupted by state-specific opto-silencing in the VTA (A) Light delivery during NREM sleep did not affect the amount of time spent in different vigilance states for Vgat-cre -ArchT (orange) or Dat-cre -ArchT (purple) mice (student’s t -tests did not reveal any significant difference between groups for any vigilance state).
…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…However, acute opto-inhibition during wake, did affect consummatory licking behavior similarly to what has been previously described for Vgat ( Van Zessen et al., 2012 ) and Dat ( Hughes et al., 2020 ; Lee et al., 2020 ) neurons ( Figure S4 ). In addition, chronic opto-inhibition of each population during rest (laser on continuously for 4 h, beginning in quiet wake) did alter sleep architecture in drastically opposing ways, consistent with chemogenetic and sustained opto-manipulation results from previous studies ( Eban-Rothschild et al., 2016 ; Yu et al., 2019a , b ; Figure S5 ).
Figure 4 Sleep was not disrupted by state-specific opto-silencing in the VTA (A) Light delivery during NREM sleep did not affect the amount of time spent in different vigilance states for Vgat-cre -ArchT (orange) or Dat-cre -ArchT (purple) mice (student’s t -tests did not reveal any significant difference between groups for any vigilance state).
…”
Section: Resultssupporting
confidence: 87%
“…Because it has been shown that VTA populations play a role in transitions between sleep and wakefulness, we wanted to ensure that our optogenetic approach did not directly disrupt sleep architecture; therefore, we avoided optogenetic activation because previous work has demonstrated that for both the dopaminergic ( Eban-Rothschild et al., 2016 ) and GABAergic ( Yu et al., 2019a , b ) populations, this causes sleep state transitions within seconds of stimulation. With our unilateral opto-inhibition approach, we found that state-specific optical manipulation did not alter the time spent in each arousal state, compared to wild-type no-laser controls or non-opsin controls, which received the same laser treatment ( Figures 4 A and 4B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 GABAergic VTA neurons communicate locally within the VTA but also give rise to prominent projections to other parts of the brain 2 , 3 and regulate sleep, mania-like behavior, and innate defensive responses. 4–6 In 2005, Perrotti et al found that chronic administration of psychostimulants, such as cocaine and amphetamine, to rats could induce the expression of the transcription factor Delta FosB within a group of GABAergic neurons in the posterior VTA, but no expression was observed in the anterior VTA, the traditional VTA area. 7 Jhou et al also reported GABAergic neurons lateral to the median raphe nucleus and caudal to the VTA regulate freezing and other passive aversive responses via projections to midbrain DAergic neurons.…”
Section: Introductionmentioning
confidence: 99%